Efficiency of Dodonaea viscosa to phytoremediation of heavy metals contaminated soil - Al-Dulaimi, Shaimaa Hadi; Mamand, Shilan Farhad; Al-Fhdawi, Ahmed Attalah Hassan (Iraqi Journal of Science, 2025)
The study was designed to investigate Dodonaea viscosa efficiency in the uptake, translocation, and accumulation of Cadmium, Zinc, and Copper metals from contaminated soils. The phytoremediation of Dodonaea was assessed by cultivating the plant in pots. Plants were cultivated in an experiment with an average diameter of 26.5 cm and height of 30 cm for six months under different treatments of Cd, Zn, and Cu. Metals concentrations in soil and plant parts were measured using the XRF instrument. Bioaccumulation factor (BF), translocation factor (TF), and Contamination factor (CF) were values. The results indicated that D. viscosa absorbed metals from the soil in the following order: roots > shoots > soil, and three metals are effectively restricted in the root. For BF the order was Zn >Cu > Cd, in which D. viscosa absorbed heavy metals from the soil to their roots. TF for the Cd, Zn, and Cu metals were less than one. For CF results, the highest value was recorded under D4 for Cd in root 31.0 ±1.86 mg/kg, and the lowest level was 0.276 ±0.08 mg/kg under D1 for Zn in soil.